Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0274665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of closed and permanent stoma on disease course, psychological well-being and working capacity in Swiss IBD cohort study patients

Abstract: ¶ Membership of the Swiss IBD cohort study is provided in the Acknowledgements.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This novel study contributes to the growing psychological research looking at the impact of having an intestinal stoma in adults on well‐being and QoL. It is one of the few known UK studies to compare stoma and non‐stoma participants on a range of psychological measures (Bianchi et al., 2022 ; Silva et al., 2017 ; Temprado Albalat et al., 2018 ). The findings elucidate a better understanding of the psychological needs of those living with a stoma and establish the importance of stoma‐related factors such as the early years following surgery and those experiencing frequent leaks, as being detrimental to psychological well‐being and QoL in some participants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This novel study contributes to the growing psychological research looking at the impact of having an intestinal stoma in adults on well‐being and QoL. It is one of the few known UK studies to compare stoma and non‐stoma participants on a range of psychological measures (Bianchi et al., 2022 ; Silva et al., 2017 ; Temprado Albalat et al., 2018 ). The findings elucidate a better understanding of the psychological needs of those living with a stoma and establish the importance of stoma‐related factors such as the early years following surgery and those experiencing frequent leaks, as being detrimental to psychological well‐being and QoL in some participants.…”
Section: Discussionmentioning
confidence: 97%
“…Polidano et al., 2020 ) and the lived experience assessed by Interpretative Phenomenological Approach (IPA) (Horgan et al., 2020 ; Jordan et al., 2018 ). Reducing psychological distress is part of the UK healthcare policy for stoma patients (Department of Health, 2011 ) and remains a challenge due to a lack of understanding of psychological health needs (Bianchi et al., 2022 ; Wallace, 2016 ), which was addressed in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…However, other patients are unable to retract for various reasons and suffer great physical and psychological damage. Some studies (8,9) have shown that permanent stoma prolongs the life of patients but reduces their quality of life. Therefore, it is crucial to understand high risk factors for permanent stoma so that surgeons can appropriate counsel patients.…”
Section: Introductionmentioning
confidence: 99%